2017
DOI: 10.1091/mbc.e16-08-0583
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing molecular motors for nanoscale pulldown in live cells

Abstract: Nanoscale pulldown (NanoSPD) miniaturizes the concept of affinity pulldown to detect protein–protein interactions in live cells. NanoSPD hijacks the myosin-based intracellular trafficking machinery to assess interactions under physiological buffer conditions and is microscopy-based, allowing for sensitive detection and quantification.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 70 publications
1
42
1
Order By: Relevance
“…The images were converted to tagged image file format (TIFF). Filopodia were then selected and signals at their tips quantified using the FIJI-based procedure and MATLAB software described by Bird and colleagues (NanoSPD [48]). 33 cells representing 3 independent experiments were selected for each condition, and 126 (MYC) versus 225 (MYC:GPSM2) filopodia that passed the selection process were analyzed.…”
Section: Immunofluorescence Image Analysismentioning
confidence: 99%
“…The images were converted to tagged image file format (TIFF). Filopodia were then selected and signals at their tips quantified using the FIJI-based procedure and MATLAB software described by Bird and colleagues (NanoSPD [48]). 33 cells representing 3 independent experiments were selected for each condition, and 126 (MYC) versus 225 (MYC:GPSM2) filopodia that passed the selection process were analyzed.…”
Section: Immunofluorescence Image Analysismentioning
confidence: 99%
“…Eventually, Chd7 expression becomes enriched in specific cells and tissues, especially in organs where malformations are known to occur in CHARGE. CHD7 is localized primarily to the nucleus, although a recent study suggested it may also localize to inner ear stereocilia [Bird et al, 2017]. Chd7 expression in mouse neural tissues likely reflects its important functions in a wide variety of peripheral and central nervous system regions.…”
Section: Chd7 Gene Structure Expression Evolutionary Conservation mentioning
confidence: 99%
“…To further explore the molecular mechanism of CIB2-mediated mTORC1 modulation, we assessed direct interactions between CIB2 and TSC1, TSC2, mTORC1-specifc subunit Raptor, mTOR kinase, and Rheb, using a previously reported nanoscale pulldown 2.0 (NanoSPD) quantitative interaction assay 32 . NanoSPD utilizes a construct (nanoTRAP) consisting of GFP nanobody fused with the heavy meromyosin (HMM domain) of myosin 10 (myo10 HMM -GFP nanobody).…”
Section: Cib2 Forms a Tripartite Complex With Raptor-mtormentioning
confidence: 99%